2014
DOI: 10.1111/vop.12236
|View full text |Cite
|
Sign up to set email alerts
|

Specular microscopy to determine corneal endothelial cell morphology and morphometry in chinchillas (Chinchilla lanigera) in vivo

Abstract: The results suggested that chinchilla corneal endothelium undergoes age-related changes. Moreover, with advancing age, the mean cell area increased and cell density decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 29 publications
7
33
0
6
Order By: Relevance
“…Using images obtained by specular microscopy, it is possible to examine the corneal endothelium and obtain data related to endothelial cell density and morphology. This technique has been used to quantify endothelial parameters in humans and other animal species including pigs (TAMAYO-ARANGO et al, 2009), rabbits (SAILSTAD & PEIFFER, 1981;OJEDA et al, 2001), dogs (GWIN et al, 1982;PIGATTO et al, 2006;RODRIGUES et al, 2006), horses (ANDREW et al, 2001;LEDBETTER & SCARLETT, 2009), llamas and alpacas (ANDREW et al, 2002), chinchillas (BERCHT et al, 2015), and cats (FRANZEN et al, 2010), among others. The high cost of specular microscopes and the difficulty in obtaining good images in injured endothelial areas are common challenges or barriers to the use of this technique (ANDREW et al, 2001;PIGATTO et al, 2005a;SAAD et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using images obtained by specular microscopy, it is possible to examine the corneal endothelium and obtain data related to endothelial cell density and morphology. This technique has been used to quantify endothelial parameters in humans and other animal species including pigs (TAMAYO-ARANGO et al, 2009), rabbits (SAILSTAD & PEIFFER, 1981;OJEDA et al, 2001), dogs (GWIN et al, 1982;PIGATTO et al, 2006;RODRIGUES et al, 2006), horses (ANDREW et al, 2001;LEDBETTER & SCARLETT, 2009), llamas and alpacas (ANDREW et al, 2002), chinchillas (BERCHT et al, 2015), and cats (FRANZEN et al, 2010), among others. The high cost of specular microscopes and the difficulty in obtaining good images in injured endothelial areas are common challenges or barriers to the use of this technique (ANDREW et al, 2001;PIGATTO et al, 2005a;SAAD et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The results observed in this study show that normal swine corneal endothelium consisted of a continuous monolayer with mainly hexagonal cells, but were also found cells with five sides and with seven sides. Previous studies conducted involving vertebrate animals have shown that there is predominance of cells with hexagonal shape and, in lower proportion, there is presence of five-and seven-sided cells (Collin & Collin, 1998, Pigatto et al 2005, Gum et al 2007, Tamayo-Arango et al 2009, Bercht et al 2015, Coyo, et al 2015.…”
Section: Discussionmentioning
confidence: 97%
“…The parameters evaluated by specular microscopy did not differ significantly between the right eye bulb and the left eye bulb from the same pig. It is well established that the density of endothelial cells from both healthy eyes of the same patient is similar (Pigatto et al 2005, Gum et al 2007, Tamayo-Arango et al 2009, Bercht et al 2015, Coyo, et al 2015. The examination of specular microscopy performed before starting of the experiment allowed to only be selected healthy eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that there is no cellular retraction and it can be used in animals and living humans, specular microscopy is considered the gold standard technique for assessing the corneal endothelium in people and animals (MORITA, 1995;ABIB & BARRETO, 2001;PIGATTO et al, 2006;PIGATTO et al, 2008;FRANZEN et al, 2010;BERCHT et al, 2015;ALBUQUERQUE et al, 2015;COYO et al, 2016). Specular microscopy has also been employed in the evaluation of dogs undergoing cataract removal surgery (NAGATSUYU et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Specular microscopy is among the most reliable techniques for analysing the corneal endothelium (ABIB & BARRETO, 2001;NAGATSUYU et al, 2014). Normal endothelial parameters have already been established in some species using a specular microscope, including: humans, sheep, dogs, monkeys, horses, cats, and others (ABIB & BARRETO, 2001;ANDREW, S. et al 2001;PIGATTO et al, 2006;PIGATTO et al, 2008;FRANZEN et al, 2010;BERCHT et al, 2015;COYO et al, 2016;TERZARIOL et al, 2016). Furthermore, specular microscopy is beginning to be used as part of the ophthalmic examination before and after cataract removal procedures in dogs (NAGATSUYU et al, 2014).…”
Section: Introductionmentioning
confidence: 99%